The legal order of electronic records management - Giménez-Chornet, Vicent; Hernández Olivera, Luis M. (Tábula, 2020)
We are in a period of transition from a paper-based administration to an electronic format one. We are undergoing a digital revolution that has an impact not only on the media and formats but also, and in a relevant way, on new models of process and management, demanding other skills and competencies of the staff performing more complex technical tasks. Interdisciplinarity in learning is becoming more and more necessary for the resolution of the challenges of our time. The legislative framework should also be adapted to regulating a new management model and validating electronic documents.Without paper or other traditional media, the evidence of society and administrations would not